1999
DOI: 10.1038/sj.bmt.1701758
|View full text |Cite
|
Sign up to set email alerts
|

The role of thiotepa in allogeneic bone marrow transplantation for genetic diseases

Abstract: Summary:Graft-versus-host disease (GVHD), graft rejection, disease recurrence and long-term toxicity remain significant obstacles to successful allogeneic bone marrow transplantation (BMT) in children with genetic diseases. In an attempt to improve results, we used a preparative regimen consisting of three alkylating agents, busulfan (BU), thiotepa (TTP) and cyclophosphamide (CY), for T cell-depleted allogeneic bone marrow transplantation instead of the conventional BU-CY protocol. The effect of this intensifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Thiotepa is a potent immunosuppressive and myelosuppressive drug and has been successfully used with melphalan (49–51). It has promoted engraftment in murine transplant models (52, 53) as well as in clinical studies of T cell depleted HSCT and UCBT (5456). Hydroxyurea can induce cycling of the stem cell pool potentially sensitizing them to melphalan and thiotepa (57).…”
Section: Discussionmentioning
confidence: 99%
“…Thiotepa is a potent immunosuppressive and myelosuppressive drug and has been successfully used with melphalan (49–51). It has promoted engraftment in murine transplant models (52, 53) as well as in clinical studies of T cell depleted HSCT and UCBT (5456). Hydroxyurea can induce cycling of the stem cell pool potentially sensitizing them to melphalan and thiotepa (57).…”
Section: Discussionmentioning
confidence: 99%
“…It was necessary to modify the regimen to achieve more effective eradication of the patients' stem cells and reduce disease recurrence without increasing regimen-related toxicity. Rosales et al [8] reported that the thiotepa in BMT for genetic diseases might provide a prospective conditioning followed by T-cell depletion. In our patients, PBSC was infused without manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Between the years 2003 and 2008, 16 patients who had thalassemia recurrence following graft failure after the first graft were prospectively enrolled in this study. The median patient age was 9 years (range, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and the median donor age was 16 years (range, 2-29). Patient characteristics at the time of second transplantation are summarized in Table 1.…”
Section: Characteristics Of the Patientsmentioning
confidence: 99%